Tolerância de porta-enxertos de videira (Vittis spp.) à saturação de alumínio - Fráguas, José Carlos; de Araújo Lopes do Amaral, Flávio; Braga, José Mário; Cardoso, Antônio Américo (Revista Ceres, 2025)
The effect os six levels of soil exchangeable aluminum (Al) on the behaviour of five rootstock cultivars of grape (Vittis spp.) was studied under greenhouse conditions.